Comparison of Flap Thickness, Visual Outcomes, and Higher Order Aberrations in Eyes that Underwent LASIK Flap Creation using a Femtosecond Laser Versus a Mechanical Microkeratome - Rachelle C. Perez, MD; Emerson M. Cruz, MD; Albert G. Dela Cruz, Jr., MD; Robert Edward T. Ang, MD (Philippine Journal of Ophthalmology)
Objective: To compare the predictability of flap thickness, visual and refractive outcomes, and higher order aberrations in eyes that underwent myopic LASIK using either a Technolas femtosecond laser or a Zyoptix XP mechanical microkeratome for flap creation.